Threat evaluation of Carex chordorrhiza L.f. in northern Poland - Bloch-Orłowska, Joanna (Biodiversity: Research and Conservation, 2006)
On the basis of published and unpublished data as well as the own study results the threat status of Carex chordorrhiza in the area of its declining core geographical range in northern Poland has been evaluated. In the most western part of the studied area String sedge is believed to be regionally extinct (RE). In the central part the species has been classified as an endangered species (EN), while in northeastern part of Poland it has been ranked into the group of near threatened taxa (NT).